Prediction of instability of slopes in an opencast mine over old surface and underground workings - Singh T.N.; Singh D.P. (My University, 2025)
Jharia coalfield is a chief storehouse of prime coking coal in India, Earlier, many shallow seams were exploited by surface mining but when this method became uneconomical the mine operators resorted to underground method. However, due to various geotechnical problems, it was not possible to fully extract coal by underground method. Opencast mining is now being planned for extraction of coal locked in partially worked coal seam for ensuring maximum recovery. The major problem envisaged in conducting opencast mining in such areas will be the stability of slope. In this paper, the technique adopted for simulation of 144 m thick section of rockmass in equivalent material model is outlined. Old shallow surface excavation upto 33.0 m and later on underground workings were simulated in coal seam II/III. The span of the void was 160 m. An opencast excavation was conducted for recovering locked coal. The behaviour of slopes are reported here. © 1992, Taylor & Francis Group, LLC. All rights reserved.